Behavior‐ and characteristic‐based price discrimination. Issue 2 (12th February 2018) - Colombo, Stefano
Abstract: We develop a model of behavior‐ and characteristic‐based discriminatory pricing where consumers are heterogeneous both in tastes and in price sensitivity. Each firm is able to distinguish between the consumers that have bought from it and those that have bought from the rival. Furthermore, each firm learns the price sensitivity of their own consumers. We show that using this additional information may yield higher profits than uniform pricing provided that consumers are heterogeneous enough with respect to price sensitivity. We also discuss consumer surplus implications of such behavior‐ and characteristic‐based price discrimination, and we show that the impact of price discrimination depends on both the consumer type and the level of consumers' heterogeneity.